1999
DOI: 10.1063/1.123468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion mass on the evolution of extended defects during annealing of MeV ion-implanted p-type Si

Abstract: Articles you may be interested inPhotoluminescence and structural studies on extended defect evolution during high-temperature processing of ion-implanted epitaxial silicon Photoluminescence, deep level transient spectroscopy and transmission electron microscopy measurements on MeV self-ion implanted and annealed n-type silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…However, the TEM characterization of these three different samples in this study clearly show that for different species with similar damage distribution, the defects formed are different and dislocation loops are preferentially nucleated in samples implanted with higher mass species. 8 The observations related to preferential nucleation of loops for heavier mass species appear to be a direct result of the denser cascades created by implantation of the heavier species consistent with both experimental evidence 19 and MD simulations. 20 Even though the dose in our experiments has been adjusted to minimize differences in average damage distribution, the dense cascades created by the heavier mass species may have introduced some local amorphous regions at the peak of the damage distribution.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…However, the TEM characterization of these three different samples in this study clearly show that for different species with similar damage distribution, the defects formed are different and dislocation loops are preferentially nucleated in samples implanted with higher mass species. 8 The observations related to preferential nucleation of loops for heavier mass species appear to be a direct result of the denser cascades created by implantation of the heavier species consistent with both experimental evidence 19 and MD simulations. 20 Even though the dose in our experiments has been adjusted to minimize differences in average damage distribution, the dense cascades created by the heavier mass species may have introduced some local amorphous regions at the peak of the damage distribution.…”
Section: Discussionsupporting
confidence: 63%
“…Fatima et al 2,8 have determined the threshold doses corresponding to the transformation from point defects to extended defects in annealed samples. The threshold dose was shown to depend more strongly on the damage production than on the dose of the implant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently there have been several reports on electrically active defects observed in self-ion implanted Si after annealing at temperatures above 500°C. [1][2][3][4] Analyses of the deep level transient spectroscopy ͑DLTS͒ spectra revealed that most of the defect levels observed after post-implantation annealing at temperatures between 500 and 750°C are related to Si self-interstitial clusters. 1 For implant doses of у1ϫ10 13 cm Ϫ2 , the clusters appear to transform between electronic configurations and comparison of the thermal evolution behavior of these defect levels with transmission electron microscopy ͑TEM͒ analyses suggest that the small interstitial clusters are either the precusors of the ͕311͖ defects or that they compete with ͕311͖ defects as sinks for self-interstitials.…”
mentioning
confidence: 99%